PERILAKU PEMIJAHAN TERIPANG PASIR (HOLOTHURIA SCABRA) BERDASARKAN FAKTOR LINGKUNGAN (SUHU) DI DESA OHOI LETMAN KECAMATAN KEI KECIL KABUPATEN MALUKU TENGGARA - Adolof S Narayaman (BIOPENDIX, 2014)
Background: Sea Cucumber (Holothuria scabra) is one of the export commodities from fisheries sector which has decreased production and resource conservation. Spawning sea cucumbers as a first step in the provision of seeds on the cultivation that has been successfully done naturally, but the frequency of spawning is still very low. Method: Treatment of mother of sea cucumber which is selected and taken as sample which is 8 tail and have always active behavior. Mother of sea cucumber then selected by length and weight of sea cucumber. Result: Spawning behavior displayed by sea cucumbers during spawning based on environmental factors (temperature) by raising the temperature (boiling) seawater or temperature shock. So at an initial temperature of 27 ° C the behavior of sea cucumbers looks very active. Then with an interval of ± 30 minutes the temperature increased to 28 ° C, seen the behavior shown that the sea cucumbers do the process of elongation of the body, so that the sea cucumber looks different from before Conclusion: Male breeding spawning on the back of the body (posterior), the mother cucumber raises the height of the head or the front of the body (anterior) which visible a bulge that then removes the sperm that looks like white smoke in the water. With an interval of 10 minutes a female parent appeared to be in the same temperature and the same breeding method the mature female was removing the egg.